Reaching a cell monolayer at the end of hiPSC differentiation enhances neural crest lineage commitment - Filipa M. Duarte; Jeroen van de Peppel; Irene M.J. Mathijssen; Johan W. van Neck (PLoS ONE, 2025)
Neural crest stem cells (NCSCs) compose a highly migratory, multipotent, stem cell population arising from the neural plate border of the embryonic ectoderm. Investigating the development of NCSCs is critical in understanding both embryonic development and abnormal events that underlie neurocristopathies. Suggested seeding densities in in vitro human induced pluripotent stem cells (hiPSCs) differentiation protocols, varying between 10,000 cells/cm2 and 200,000 cells/cm2, demonstrate a lack of consensus on the optimal conditions to obtain NCSCs. Aiming to maximize the differentiation efficiency of hiPSCs towards the NCSCs lineage, we investigated the effect of the initial seeding density on NCSCs lineage commitment, both in fibroblast- and human peripheral blood mononuclear cell (PBMC)-derived hiPSCs. Cultures were characterized with gene and protein expression analysis assessing stemness (OCT3/4 and NANOG), neural crest identity (SNAI2 and SOX10) and neuroectoderm identity (PAX6 and SOX1). We demonstrate that reaching a confluent monolayer of cells by the end of the differentiating protocol is crucial to obtaining NCSCs from hiPSCs. To achieve this, our results indicated 17,000 cells/cm2 is the optimal initial seeding density. Under this protocol, a confluent monolayer was reached after 8 days of differentiation and an average of 89% SOX10 positive cells were obtained. The fold change of SNAI2 and SOX10 expression was 11-fold and 17-fold higher, respectively, in cultures seeded with 17,000 cells/cm2, compared to the highest tested density of 200,000 cells/cm2. In contrast, seeding 200,000 cells/cm2 induced neuroectoderm-like cells, confirmed by an average of 45% of cells marking positive for PAX6. With this work, we demonstrate the importance of achieving cellular confluency during NCSCs differentiation.